Gagasan Pengaturan Artificial Intelligence Sebagai Subjek Hukum Di Indonesia - Nada, Fatimah; Abqori, Favian Faruq; Fatimah.RH, Dinda Ratu Nur; Rahadiyan, Inda; Riswandi, Budi Agus (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
This research explores the possibility and concept of regulating Artificial Intelligence (AI) as a legal subject in Indonesia. With rapid advancements in AI technology, AI can perform tasks requiring human-like intelligence, raising questions about its legal status. In some countries, AI has been used to assist in resolving legal issues, demonstrating its potential to be considered a legal subject. In Indonesia's positive law, legal subjects currently include humans (natural persons) and legal entities (legal persons). However, since AI can perform actions that resemble or replace human work, AI is considered to have rights and obligations that need to be regulated by legal norms. This study uses a normative juridical method to analyze existing regulations and the potential regulation of AI as a legal subject. The results show that although AI has significant capabilities, regulating AI as a legal subject faces considerable challenges. The study concludes that regulating AI as a legal subject in Indonesia requires in-depth study and multidisciplinary discussion. Appropriate and balanced regulations are needed to protect the rights and interests of society in this digital era, given that AI continues to evolve and has the potential to bring significant changes in various sectors of life.